2011
DOI: 10.2105/ajph.2010.193656
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Lead Pollution and Elevated Blood Lead Levels Among Children in a Rural Area of China

Abstract: Our data show that the lead industry caused serious environmental pollution that led to high BLLs in children living nearby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 15 publications
2
25
1
3
Order By: Relevance
“…Exposure to excess toxic elements such as lead in the environmental that increases the production of free radicals, leads to decrease the availability of bioelements necessary for antioxidant defense mechanisms, So acute and chronic low-level lead exposure has been shown to result in adverse health effects [16] [17]. As well our results agree with Line ,et al who explained the elevated lead level observed in some rural areas by the fact that some villages are polluted with high concentration of lead in soil and household dust that subsequently carry lead exposure to the population there causing elevated lead level [18] [19] [20]. Air polluted by oxides and minerals more dangerous on human health where through breathing pollutants move by one hundred percent to human blood and features Baghdad city like all cities abundance cars which use fuel have dangerous toxic which include lead which effects significantly on the patients , elderly and pregnant women posing a risk to fetuses ,High lead level in the blood causes anemia and lakes of hemoglobin in the blood this may lead to liver kidney and brain damage and it was up to the central nervous system [21].…”
Section: Resultssupporting
confidence: 89%
“…Exposure to excess toxic elements such as lead in the environmental that increases the production of free radicals, leads to decrease the availability of bioelements necessary for antioxidant defense mechanisms, So acute and chronic low-level lead exposure has been shown to result in adverse health effects [16] [17]. As well our results agree with Line ,et al who explained the elevated lead level observed in some rural areas by the fact that some villages are polluted with high concentration of lead in soil and household dust that subsequently carry lead exposure to the population there causing elevated lead level [18] [19] [20]. Air polluted by oxides and minerals more dangerous on human health where through breathing pollutants move by one hundred percent to human blood and features Baghdad city like all cities abundance cars which use fuel have dangerous toxic which include lead which effects significantly on the patients , elderly and pregnant women posing a risk to fetuses ,High lead level in the blood causes anemia and lakes of hemoglobin in the blood this may lead to liver kidney and brain damage and it was up to the central nervous system [21].…”
Section: Resultssupporting
confidence: 89%
“…In addition, it is likely that lead impairs child growth and development, particularly when lead exposure occurs in the prenatal period (Needleman, 2004). Although there have been concerted public health interventions over the past several decades, the general public continues to be exposed to low levels of lead because of its widespread use (Lin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the Fujian Province of southeast China, Pb is one of the most abundant mineral resources. According to a study performed in 2007, environmental pollution from activities such as mining, separating, smelting, and transportation by more than 100 Pbrelated enterprises resulted in high BLLs among the children in the surrounding population (Lin et al, 2011). More than 4000 Chinese children have been affected by Pb poisoning since 2009 (Ji et al, 2011).…”
Section: Specific Cases Of Children At Riskmentioning
confidence: 99%